1984
DOI: 10.1203/00006450-198408000-00103
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lung Development in Age Related Susceptibility of Ferrets to Influenza Virus

Abstract: We present two cases of acute r enal failure associated wi t h a microangiopathic haemol ytic anaemia followin g pneu mococcal infections. In both children t here was evidence o.f red cell T-poly-egglutinability (bsing msn i f es t initially as discrspant ABO blood group ing) . In one child pneumococci were i so l at e d from the blood whilst in the other there wee antigenic ev idence of a recent pneumococcal i nf ec t i on . Both ch ildren had a period of oliguric renal failure requiring dialysis. Prostagland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Influenza infection may involve the lower respiratory tract in some susceptible animals [1,59]. Usually, influenza virus is confined to the bronchial and bronchiolar tissues [53,60]. The disease may be fatal in 1-to 2-day-old ferret kits secondary to bronchiolitis, pneumonia, and aspiration of material from the upper respiratory tract [57,61,62].…”
Section: Pathogenesis and Clinical Signsmentioning
confidence: 99%
“…Influenza infection may involve the lower respiratory tract in some susceptible animals [1,59]. Usually, influenza virus is confined to the bronchial and bronchiolar tissues [53,60]. The disease may be fatal in 1-to 2-day-old ferret kits secondary to bronchiolitis, pneumonia, and aspiration of material from the upper respiratory tract [57,61,62].…”
Section: Pathogenesis and Clinical Signsmentioning
confidence: 99%
“…The ferret model has also been used to investigate age-related host response and disease severity to influenza virus infection both for the old [110] and young [17,18,111,112]. Ferrets were first used to investigate infant responses to influenza virus infection in the late 1970s by a group from the University of Birmingham in the United Kingdom [19,[113][114][115][116][117]. In adult ferrets, influenza virus infection with seasonal influenza virus strains typically leads to a non-fatal disease characterized by weight loss, temperature increase, and respiratory symptoms including coughing and sneezing [118,119] at varying degrees dependent on the strain.…”
Section: Ferret Modelmentioning
confidence: 99%
“…In a follow up study that compared influenza illness in newborn ferrets to 15-day old suckling ferrets, it was found that while newborn ferrets succumb to illness, 15-day old ferrets seemed resilient to fatal disease and developed pathology similar to adults [120]. Furthermore, the increased disease severity in infants was suggested to be due to an increased proportion of ciliated epithelium-lined airway when compared to the adult and 15-day old ferret lungs [19]. This suggested a rapid development of the ferret respiratory tract, which may influence influenza severity.…”
Section: Ferret Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review of infant mice studies has shown decreased T cell immune responses in infant animals [ 17 , 18 ], but studies investigating humoral and antibody responses are currently lacking. Reviewing literature from infant ferret studies has demonstrated that outcomes of influenza virus infection may be significantly dependent on ferret age post-partum [ 19 , 20 , 21 , 22 ]. These models, discussed in detail below, may be useful for future studies involving imprinting and development of immune memory so that infant-specific vaccines can be developed.…”
Section: Introductionmentioning
confidence: 99%